Implementasi Peraturan Bupati Buton Selatan Nomor 23 Tahun 2017 tentang Pemilihan Kepala Desa dalam Penyelesaian Sengketa Pemilihan Kepala Desa Serentak di Kabupaten Buton Selatan - Mili, Sumarlin La; Muhaimin, La Ode; Faharudin, Faharudin (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Settlement of disputes over the election of village heads is the attributive authority of district/city regional heads based on Article 37 Paragraph (6) of Law Number 6 of 2014 concerning Villages, which states